IJEPA dan Transformasi Industri Otomotif Indonesia - Fritscilia, Yulia; Rifai, Maulana (Jurnal Ilmiah Wahana Pendidikan, 2025)
The Indonesia-Japan Economic Partnership Agreement (IJEPA) is a bilateral economic cooperation agreement aimed at strengthening strategic relations between Indonesia and Japan across various sectors, including the automotive industry. Under the leadership of President Joko Widodo (Jokowi), who emphasizes strengthening domestic industries and increasing exports, IJEPA plays a significant role in enhancing the competitiveness of Indonesia’s national automotive sector. This study is grounded in the context of globalization and intense regional competition in the automotive industry, which requires Indonesia to improve production quality, technology, and attract more foreign investment. The objective of this research is to analyze the contribution of IJEPA in strengthening the competitiveness of Indonesia’s automotive industry, particularly during President Jokowi’s administration. The research employs a descriptive qualitative approach, with data collected through literature studies, documentation of bilateral agreements, and secondary data analysis from government reports, industry associations, and international institutions. The findings indicate that IJEPA has made a substantial contribution in boosting Japanese investment in Indonesia’s automotive sector, facilitating technology transfer, and expanding export market access to Japan. Additionally, the development of workforce training programs and the strengthening of the domestic supply chain have supported improvements in production quality. The Indonesian government, through industrial policies and investment incentives, has capitalized on the momentum of IJEPA cooperation to accelerate the transformation of the automotive industry toward electric and environmentally friendly vehicles. IJEPA serves as a vital instrument in enhancing the competitiveness of Indonesia’s automotive industry, especially in responding to global demands and the strategic policies of the Jokowi administration. Keywords: Competitiveness, Export, IJEPA, Indonesia, Automotive Industry.